2008
DOI: 10.5014/ajot.62.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Theory Use in Practice: A National Survey of Therapists Who Use the Model of Human Occupation

Abstract: Making resources more readily available and accessible to therapists might enhance the extent to which they use conceptual models such as MOHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 8 publications
3
52
0
1
Order By: Relevance
“…Occupational therapists reported that providing OBI is challenging because the client does not understand the unique role of occupational therapy nor the outcome of the intervention (Chisholm et al, 2004). From occupational therapists' perspectives, they have much less understanding of the environmental concept of objects, spaces and occupational forms, which contribute to the challenge of using OBI (Lee, Taylor, Kielhofner, & Fisher, 2008). Providing OBI requires the occupational therapist to know more about the client's context and to use appropriate interventions to achieve occupational performance goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Occupational therapists reported that providing OBI is challenging because the client does not understand the unique role of occupational therapy nor the outcome of the intervention (Chisholm et al, 2004). From occupational therapists' perspectives, they have much less understanding of the environmental concept of objects, spaces and occupational forms, which contribute to the challenge of using OBI (Lee, Taylor, Kielhofner, & Fisher, 2008). Providing OBI requires the occupational therapist to know more about the client's context and to use appropriate interventions to achieve occupational performance goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Model of Human Occupation, the first model built in Occupational Therapy with incorporated ideas from systems theory, is evidenced as the most widely used occupationbased model in all over the world (Kielhofner and Forsyth, 1997;Brown, Rodger, Brown &Roever, 2005;Haglund, Ekbladh, Thorell & Hallberg, 2000;Law&McColl, 1989;NBCOT, 7 2004;Wikeby, Lundgren & Archenholtz, 2006, cited by Lee, Taylor, Kielhofner, Fisher, 2008). …”
mentioning
confidence: 99%
“…Published in 1986 and available in 13 languages, the Role Checklist remains one of the most commonly used assessments in American occupational therapy practice. In a survey of therapists in the US, the Interest Checklist was the only other assessment ranked higher in frequency of use (Lee, Taylor, Kielhofner, & Fisher, 2008).…”
mentioning
confidence: 99%